Afghanistan's India–Pakistan dilemma: advocacy coalitions in weak states. Issue 2 (2nd April 2016) - Paliwal, Avinash
Abstract : This article seeks to examine the foreign policy behaviour of weak states in regions marked by politically turbulent geostrategic environments. An analysis of Afghanistan's foreign policy behaviour vis-à-vis Pakistan and India lends focus to this aim. India–Pakistan rivalry has gained traction as a key factor in determining Afghanistan's stability in the wake of the drawdown of Coalition forces. Missing from this debate, however, is consideration of Afghanistan's agency as a weak state with an independent set of policy preferences. Based on primary interviews with a diverse set of Afghan political actors the article outlines two competing policy advocacies: Pakistan friendly and Pakistan averse. The article argues that these advocacies are key to understanding Afghanistan's India–Pakistan dilemma. Departing from the ethnic lens used to explain Afghan politics and its regional linkages, this article shows that Kabul's relations with Islamabad determine its approach towards New Delhi regardless of ethnic rivalries. Understanding domestic Afghan narratives in this regional context is therefore imperative to adequately assess South Asia's prospective security calculus.